Flt3 Regulation in the Mononuclear Phagocyte System Promotes Ocular Neovascularization - Yushuo Gao; Yisheng Zhong; Yanji Zhu; Anna M. Demetriades; Yujuan Cai; Jikui Shen; Qing Lu; Xi Shen; Bing Xie (Journal of Ophthalmology)
Fms-like tyrosine kinase 3 (Flt3), a tyrosine kinase receptor expressed in CD34+ hematopoietic stem/progenitor cells, is important for both normal myeloid and lymphoid differentiation. It has been implicated in mice and humans for potential multilineage differentiation. We found that mice deficient in Flt3 or mice that received an Flt3 inhibitor (AC220) showed significantly reduced areas of ischemia-induced retinal neovascularization (RNV) and laser-induced choroidal NV (CNV) (P<0.05). Increased Flt3 expression at the protein level was detected in retinas of oxygen-induced retinopathy (OIR) mice at P15 and P18 during retinal NV (RNV) progression. We subsequently found that macrophages (Mphi) polarization was regulated at the site of CNV in Flt3-deficient mice. Flow cytometry analysis demonstrated that Flt3 deficiency shifted Mphi polarization towards an M2 phenotype during RNV with significant reduction in M1 cytokine expression when compared to the wild-type controls (P<0.05). Based on the above findings, we concluded that Flt3 inhibition alleviated ocular NV by promoting a Mphi polarization shift towards the M2 phenotype. Therapies targeting Flt3 may provide a new approach for the treatment of ocular NV.